Ultra-pH-Sensitive Nanoprobe Library with Broad pH Tunability and Fluorescence Emissions - Ma, Xinpeng (American Chemical Society, 2014)
[Image: see text] pH is an important physiological parameter that plays a critical role in cellular and tissue homeostasis. Conventional small molecular pH sensors (e.g., fluorescein, Lysosensor) are limited by broad pH response and restricted fluorescent emissions. Previously, we reported the development of ultra-pH-sensitive (UPS) nanoprobes with sharp pH response using fluorophores with small Stokes shifts (<40 nm). In this study, we expand the UPS design to a library of nanoprobes with operator-predetermined pH transitions and wide fluorescent emissions (400–820 nm). A copolymer strategy was employed to fine tune the hydrophobicity of the ionizable hydrophobic block, which led to a desired transition pH based on standard curves. Interestingly, matching the hydrophobicity of the monomers was critical to achieve a sharp pH transition. To overcome the fluorophore limitations, we introduced copolymers conjugated with fluorescence quenchers (FQs). In the micelle state, the FQs effectively suppressed the emission of fluorophores regardless of their Stokes shifts and further increased the fluorescence activation ratios. As a proof of concept, we generated a library of 10 nanoprobes each encoded with a unique fluorophore. The nanoprobes cover the entire physiologic range of pH (4–7.4) with 0.3 pH increments. Each nanoprobe maintained a sharp pH transition (on/off < 0.25 pH) and high fluorescence activation ratio (>50-fold between on and off states). The UPS library provides a useful toolkit to study pH regulation in many pathophysiological indications (e.g., cancer, lysosome catabolism) as well as establishing tumor-activatable systems for cancer imaging and drug delivery.